Olefin Metathesis as Key Step in the Synthesis of Bioactive Compounds: Challenges in the Total Synthesis of (-)-Kendomycin - Bicchielli, Dario; Borguet, Yannick; Delaude, Lionel; Demonceau, Albert; Dragutan, Ileana; Dragutan, Valerian; Hans, Morgan; Jossifov, Christo; Nicks, Francois; Willem, Quentin (Current Organic Synthesis, 2012)
In this short review article, we highlight the application of the olefin metathesis reaction as a key step in the total synthesis of (-)-kendomycin, a macrocyclic polyketide ansamycin exhibiting pronounced activity as an endothelin receptor antagonist and antiosteoporotic agent, as well as important antibiotic potency against multiresistant bacteria and remarkable cytotoxicity versus a series of human tumour cell lines. By selecting this example from the recent literature, we hope to illustrate the great synthetic ability of olefin metathesis, while also revealing some problems encountered in the syntheses.
Keywords: kendomycin